Distinct Colony Types Caused by Diploid Male Production in the Buff-Tailed Bumblebee Bombus terrestris - Di Pietro, Viviana; Ferreira, Helena Mendes; Van Oystaeyen, Annette; Wäckers, Felix; Wenseleers, Tom; Oliveira, Ricardo Caliari (Frontiers in Ecology and Evolution, 2022)
The buff-tailed bumblebee Bombus terrestris presents two distinct colony phenotypes in which some colonies already start producing males very early in the season, while others switch to producing sexuals much later in the season, and specialize mainly in the production of virgin queens. Despite having been extensively investigated in the past, the mechanisms underlying these two distinct phenotypes remain poorly understood. Here we use a combination of behavioral and genetic data to demonstrate that early switchers are in fact diploid male producing colonies, while late switchers produced normal, haploid males. Hence, at a proximate level, early switching to male production was caused by queens mating with males that by chance carried the same sex allele. These patterns were not the result of strong inbreeding within the study population, as the average inbreeding coefficient was very low and in fact slightly negative (-0.11). Moreover, an effect of inbreeding was further excluded because hybrids produced by crossing two distinct outbred populations also produced diploid males in early switching colonies. Finally, we found that diploid males only emerged after a first cohort of workers was produced, while we would have expected diploid males to be produced simultaneously with workers in a 50:50 ratio. We demonstrate that diploid males had a distinct cuticular hydrocarbon profile and propose that queens likely cull diploid males during early colony development to reduce the cost of diploid male production.